Efficacy of propolis-based mouthwashes on dental plaque and gingival inflammation: a systematic review - Esam Halboub; Sadeq A. Al-Maweri; Mohammed Al-Wesabi; Ahlam Al-Kamel; Anas Shamala; Amani Al-Sharani; Pradeep Koppolu (BMC Oral Health, 2020)
Abstract Background This systematic review of randomized clinical trials aimed to evaluate the available evidence regarding the efficacy of propolis-based mouthwash on dental plaque and gingival inflammation. Methods PubMed, Scopus, and Web of Science databases were searched up to November 2019. Clinical trials that evaluated the efficacy of propolis mouthwashes compared with chlorhexidine (CHX) were included. The primary outcomes comprised dental plaque and/or gingival inflammation. Two authors assessed the risk of bias using the Cochrane tool. Due to marked heterogeneity of the available data, studies were assessed qualitatively, and no metaanalysis was performed. Results Nine clinical trials, comprising 333 subjects, fulfilled the eligibility criteria. Most of the included studies showed high risk of bias. Overall, propolis mouthwashes showed good efficacy on plaque and gingivitis in all of the included studies. Out of the eight studies that reported on plaque index, 5 studies found equal efficacy of propolis and CHX in reducing plaque, two studies found superior efficacy in favor of CHX, while one study found superior efficacy in favor of propolis. Six studies assessed gingival inflammation outcome, four of which reported better results with propolis, while two studies reported comparable results. Conclusions The results suggest that propolis-based mouthwashes have potential benefits in reducing plaque and gingival inflammation. However, methodological limitations along with small sample sizes in some of the included studies weaken the strength of the evidence. Therefore, further well-designed clinical trials with large sample sizes and adequate follow-up period are recommended to discern the efficacy of propolis mouthwash on plaque and gingivitis.